PENGARUH PENERAPAN STANDAR AKUNTANSI, SISTEM PENGENDALIAN INTERNAL, KOMPETENSI SUMBER DAYA MANUSIA, TEKNOLOGI INFORMASI, DAN PERAN PENGELOLAAN KEUANAGAN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Afifah, Siti; Fadli, Fadli; Baihaqi, Baihaqi (UNIB Press, 2018)
This study aims to examine the effect of the application of government accounting standards, the implementation of government internal control system, human resource competence and utilization of information technology and the role of Financial Administration Officials-Organization of Regional Devices on the quality of local government financial statements. In this study the sample used is the Regional Government Organization of Bengkulu Province. Tests conducted on the data that was obtained from the questionnaire of 72 respondents. The technique that used to test this research are the validity test and reliability test while hypothesis testing is done by using regression analysis.The results of the study show that (1) the application of Government Accounting Standards positively influence on the quality of Local Government Financial Statements, (2) The implementation of Government Internal Control System positively influence on the quality of Local Government Financial Statements, (3) Human Resource Competence positively influence on the quality of Government Financial Report Region, (4) Utilization of Information Technology positively influence on the quality of Local Government Financial Statements, (5) The Role of Financial Administration Officials-Organization of Regional Devices positively influence on the Quality of Local Government Financial Statements.